Techniques for Data Mining Prediction in the Health Care Sector (International Journal of Innovative Research in Computer Science & Technology, 2023)
Data mining is another term for knowledge  discovery in databases (KDD). It's an interdisciplinary  field that focuses on rooting meaningful knowledge from  data in all sectors similar as health, education, and  business. Currently, with the covid epidemic affecting  everyone and rising coronavirus cases causing nursing  home beds, oxygen, vaccines and individuals to be denied  by hospitals, the health structure of the elderly is in the  spotlight. There's a wealth of information accessible in the  medical world about these diseases. Data booby-trapping  concepts may be used to prize meaningful styles from this  type of material in order to prognosticate unborn  followings. This study emphasizes on several mining  approaches that will be applied in the therapy assiduity to  achieve the stylish results.
Keywords: Mining; Classification; Clustering; Machine Learning